The effects of 8 weeks of functional strength training and blood flow restriction training on lower limb muscle strength, maximal power, and movement quality in male sprinter college athletes - Zhu, J.; Wang, J.; Chen, H.; Li, M.; Wang, Y.; Hu, Y. (Frontiers in Physiology, 2026)
Objective: Functional strength training (FST) combined with blood flow restriction (BFR) offers additional benefits in older adults and injured patients, but evidence in athletes is limited. This study aimed to determine whether adding BFR to FST improves lower limb muscle strength, power, and movement quality in male college sprinters.